Penerapan Media PPT pada Mata Pelajaran Fiqih Kelas 7 MTsN 1 Pasaman - Etri, Anjelia; Trisno, Bambang (Indonesian Research Journal on Education, 2023)
In the digital era 4.0, humans have experienced the conveniences provided by electronic digital media. the development of technology affects all aspects of human life, including education. The development of information and communication technology in the world of education brings changes in the education system for the better. By using this media, it is hoped that learning will be more effective because learning media is a tool used to convey learning materials to students so that they can easily understand learning. Students can get bored listening to the subject matter delivered by the teacher in class. So to overcome this, researchers tried to use one of the learning media, namely PowerPoint media. With Power Point media, it s hoped that the material can be conveyed properly.